Law and Justice’s ideological foundations and foreign policy objectives from the perspective of the year 2005 (Economic and Political Thought, 2016)
The article discusses the foundation of the Law and Justice’s foreignpolicy from the perspective of the year 2005. It deals with the issue of Polishhistorical policy and its role in foreign policy as well as the issue of politicalleadership. The article is also an attempt to compare the assumptions of theforeign policy of the Second Republic of Poland and Józef Piłsudski’s campto the Law and Justice’s foreign policy.